Board Structure and Stock Market Liquidity: Evidence from Saudi's Banking Industry - Almulhim, Abdulateif A (Asian Economic and Financial Review, 2022)
This paper aims to explore the impact of corporate governance on banks’ stock market liquidity. Specifically, we examine the influence of one of the most important corporate governance mechanisms, board structure, on the stock market liquidity of listed banks in Saudi Arabia. We mainly concentrate on four characteristics of board structure: board size, board independence, board meetings and board busyness, and their impact on bid–ask spread, trading volume, turnover ratio and number of trades (employed as proxies of stock liquidity). This study employs a pooled ordinary least squares (OLS) model to investigate this relationship. Furthermore, we use a lag approach and the generalized method of moments (GMM) estimation to test for endogeneity issues. The findings of the two models are the same as the main estimation model of the OLS. Using a sample of 108 observations representing all banks listed on the Saudi Stock Market (TASI) from 2010 to 2020, we find a positive and significant association between board size and board independence with stock liquidity. However, board busyness is negatively associated with stock liquidity. Furthermore, we examine the relationship between board structure and agency problems. The results show that board size and board independence reduce agency problems, whereas board busyness increases agency problems. The findings of this paper provide implications for Saudi regulators, banks’ board of directors and banks’ shareholders.